Effectiveness testing of some vegetal extracts comparing with clasical anthelmintics - Ilie M.S.,; Darabus Gh.,; Oprescu I,; Morariu S,; Narcisa Mederle,; Alina lie,; Imre K,; Florica Morariu (Medicamentul Veterinar)
We have tested the efficacy of some vegetal extracts (Parazitol –Medica Laboratories, a natural product with an anthelmintic effect and a Cucurbita sp. oil extract) compared to the classic anthelmintics (Rombendazol – Romvac and Dehelman – KRKA Slovenia) at domestic poultry, whose parasitical status had been previously established through animal killing and necropsies. Parazitol and the pumpkin oil have had a lower efficacy than the levamisole and albendazole upon the species Ascaridia galli. Heterakis gallinarum was not affected by the pumpkin oil. Parazitol have a moderate efficacy (36%), while levamisole and albendazole were very efficient (100%). The treatments with albendazole upon the cestods belonging to the genus Raillietina have had a 100% efficacy. In cestods, Parazitol had a better efficacy (57%) than the pumpkin oil (14%).